The Decoding of the Human Spirit: A Synergy of Spirituality and Character Strengths Toward Wholeness - Niemiec, Ryan M.; Russo-Netzer, Pninit; Pargament, Kenneth I. (Frontiers in Psychology, 2020)
Little attention has been given to the integral relationship between character strengths and spirituality (the search for or communing with the sacred to derive meaning and purpose). The science of character strengths has surged in recent years with hundreds of studies, yet with minimal attention to spirituality or the literature therein. At the same time, the science of spirituality has steadily unfolded over the last few decades and has offered only occasional attention to select strengths of character (e.g., humility, love, forgiveness) or the universal typology of the VIA Classification of character strengths and virtues. In this exploration, we argue that there is a robust synergy of these sciences and practices revealing that spirituality is vitally concerned with promoting character strengths. At the same time, character strengths can enhance and deepen spiritual practices, rituals, and experiences. We elaborate on how character strengths and spirituality come together in the context of the psycho-spiritual journey toward wholeness. By wholeness, we are referring to a way of being in the world, which involves a life-affirming view of oneself and the world, a capacity to see and approach life with breadth and depth and the ability to organize the life journey into a cohesive whole. We further discuss six levels by which spirituality can be integrated within the VIA Classification, including a meta-perspective in which wholeness represents a meta-strength or superordinate virtue. We frame two pathways of integration: the grounding path, in which character strengths offer tangibility and thereby deepen and enhance spirituality, and the sanctification path, in which spirituality elevates character strengths. Finally, we turn to research-based practices and examine how character strengths might facilitate and contribute to spiritual practices and, conversely, how spirituality might enhance character strength practices. Such multifaceted integration offers insight and wisdom to both areas of study and opens up new directions for psychospiritual research and practices to deepen and broaden our understanding of what it means to be human.